Forecasted consequences of simulated FAD moratoria in the Atlantic and Indian Oceans on catches and bycatches. (13th December 2016) - Escalle, Lauriane; Gaertner, Daniel; Chavance, Pierre; Delgado de Molina, Alicia; Ariz, Javier; Mérigot, Bastien
Abstract : Given the increasingly extensive use of drifting fish aggregation devices (FADs) by the purse-seine fisheries targeting tropical tunas, fishing effort restrictions have been introduced to manage tropical tuna stocks. However, these measures are focused on the protection of juvenile tunas and do not take account of the potential impact on bycatch or associated megafauna (whales and whale sharks). An iterative "fishing-day" Monte Carlo simulation model was developed to investigate the consequences on tropical tunas and bycatch of introducing extensive area 6-month moratoria on FAD activities. The model allowed for variability in a range of plausible values of the parameters characterizing the fishing operations conducted by European purse-seiners in the eastern tropical Atlantic and western Indian Oceans for the period 2005–2014. Monte Carlo simulations, using probabilities based on these fishery data, were carried out for the French and Spanish fishing fleets separately to account for differences in fishing strategies. The models predicted a decrease in FAD sets and an increase in free school sets. As a consequence, the catch of small tuna (<10 kg) decreased while the catch of large tuna (≥10 kg) increased, leading to an overall increase in tuna catch of 100–200 tons/year/vessel in the Atlantic Ocean, and a decrease of 400–1500 tons/year/vessel in the Indian Ocean. The bycatch decreased in the Indian Ocean, while in the Atlantic Ocean billfishes, turtles and chondrichthyans bycatch increased slightly and other bony fishes decreased. Because fishing practices were modified, whale and whale shark associated sets increased slightly in the Indian Ocean.